2016
DOI: 10.17576/pengurusan-2016-48-04
|View full text |Cite
|
Sign up to set email alerts
|

Do Managers Reappoint Auditor for Related Party Transactions? Evidence from Selected East Asian Countries

Abstract: We study the association between auditor reappointment (initial relationship stage), including recurring auditor appointment over several consecutive years (close relationship stage) and company engagement in related-party transactions (RPTs) for selected listed companies from Hong Kong, Malaysia, Singapore and Thailand. The results show that auditor reappointment has significant and negative associations with company engagement in RPTs. By contrast, the close ACR relationship increases company engagement in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 56 publications
(95 reference statements)
3
19
0
Order By: Relevance
“…These findings support the argument that rotation could decrease audit quality due to competency issues where new auditors are not too familiar with their clients (Fitriany et al, 2016). On the other hand, several other studies have found the opposite results, which deduce that auditor rotation could increase audit quality (Kurnianingsih and Rohman (2014); Carey and Simnett (2006), Rahmat and Ali (2016), and Rickett et al (2016); Junaidi et al (2016)) These findings support the argument that audit firm rotation could improve audit quality because it increases the independence of auditors. Hence, these studies' inconclusive results encourage the importance of further investigation with a better dataset and methodology in this specific area for contributing more towards the ongoing debate.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings support the argument that rotation could decrease audit quality due to competency issues where new auditors are not too familiar with their clients (Fitriany et al, 2016). On the other hand, several other studies have found the opposite results, which deduce that auditor rotation could increase audit quality (Kurnianingsih and Rohman (2014); Carey and Simnett (2006), Rahmat and Ali (2016), and Rickett et al (2016); Junaidi et al (2016)) These findings support the argument that audit firm rotation could improve audit quality because it increases the independence of auditors. Hence, these studies' inconclusive results encourage the importance of further investigation with a better dataset and methodology in this specific area for contributing more towards the ongoing debate.…”
Section: Introductionsupporting
confidence: 73%
“…More specifically, Corbella et al claim that the audit firm rotation raises the audit quality in clients audited by non-Big 4. In addition, Rahmat and Ali (2016) also argue that the established relationship created by auditor reappointment may intensify client engagement in related party transactions and interfere with auditors' independent judgment. Auditor rotation is also needed to ensure that client complies with the law as well as to incur fresh approaches to the audit process (Teh et al, 2016).…”
Section: Impact Of Audit Firm Tenure and Rotation On Audit Qualitymentioning
confidence: 99%
“…The regression model is as follows: Where, RPType it represents a vector that describes RPT and RPT-conflict. RPT, a total magnitude of RPTs disclosed in the financial statement in a year t, scaled by the beginning of total assets of year t. This measurement is consistent with Kohlbeck and Mayhew (2010) and Rahmat and Ali (2016). All RPTs are considered as representing opportunistic transactions, which probably used as tools to maximize personal benefits.…”
Section: Regression Model and Variable Measurementsmentioning
confidence: 95%
“…The objectives are examined by using 548 firms listed in Bursa Malaysia over a three-year period from 2012 to 2014 that consisted of a total of 1,550 observations. These firms are selected as RPTs are rampant among listed firms in Malaysia (Abdul Wahab et al 2011;Rahmat & Ali 2016). The environment and landscape of business in Malaysia are conducive for firms to engage in RPTs due to several reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation